Temple Grandin - Monger, Christopher; Ferguson, Scott; Jackson, Mick.; O'Hara, Catherine; Strathairn, David; Ormond, Julia; Danes, Claire, 1979-; Merritt Johnson, William; Grandin, Temple; Grandin, Temple; Home Box Office (Firm); Ruby Films (Firm) (Burbank, CA : HBO Films, 2010)
An engaging portrait of an autistic young woman who became, through timely mentoring and sheer force of will, one of America's most remarkable success stories.
Based on the book Emergence by Temple Grandin and Margaret Scariano and Thinking in pictures by Temple Grandin.
Special features: The making of Temple Grandin; audio commentary with Dr. Temple Grandin, director Mick Jackson, and writer Christopher Monger.
Director of photography, Ivan Strasburg ; film editor, Leo Trombetta.
Claire Danes, Catherine O'Hara, David Strathairn, Julia Ormond.
CHV Rating: 14A.
DVD, region 1, widescreen (16:9) presentation ; Dolby digital, English 5.1, Spanish 2.0.
Keywords: Grandin, Temple -- Drama; Animal scientists -- Drama; Autistic people -- Drama; Feature films; Video recordings for hard of hearing people; Biographical films; Made-for-TV movies